Key Stakeholders in Addressing Gaps in Occupational Health in India: Areas Where IAPSM Can Play a Crucial Role - Purushottam Giri; Pooja Goyal (Healthline)
Industrialization has been a driving force behind India’s economic growth, transforming the nation into one of the world’s largest industrial economies. Over the past few decades, the expansion of industries ranging from manufacturing to construction has contributed significantly to employment opportunities, infrastructure development, and technological advancements. According to the International Labour Organization (ILO), India has one of the highest rates of work-related fatalities in the world, with tens of thousands of deaths reported annually due to industrial accidents and occupational diseases. There is a need for urgent attention to occupational safety and health issues.